O01.5 Efficacy of RG1-VLP Vaccination Against Genital and Cutaneous Human Papillomaviruses in Vitro and in Vivo. (13th July 2013) - Schellenbacher, C; Kwak, K; Fink, D; Shafti-Keramat, S; Huber, B; Jindra, C; Roden, R; Kirnbauer, R
Abstract : Licensed human papillomavirus (HPV) vaccines, based on virus-like particles (VLP) self-assembled from major capsid protein L1, afford type-restricted protection against types 16/18/6/11 (or 16/18 for the bivalent vaccine), which cause 70% of cervical carcinomas (Cxca) and 90% of genital warts. However, they do not protect against less prevalent high-risk types causing 30% of CxCa, or cutaneous HPV. The minor capsid protein L2 confers low-level immunity to type-common epitopes. Chimeric RG1-VLP presenting HPV16L2 amino acids 17–36 (RG1 epitope) within the DE-surface loop of HPV16L1 induce cross-neutralisation in vitro . We hypothesised, that RG1-VLP vaccination protects against a large spectrum of mucosal and cutaneous HPV infections in vivo . L2-specific antibody and CTL responses in RG1-VLP vaccinated rabbits were determined by ELISA and ELISPOT assays. Cross-neutralisation was analysed using native or pseudovirion (PsV) assays. Vaccine efficacy in vivo was determined in a mouse genital challenge model. Immunization with RG1-VLP adjuvanted with human-applicable alum-MPL induced robust L2 antibodies (ELISA titers 2, 500–12, 500), which cross-neutralised mucosal high-risk HPV26/33/35/39/68/59/68/73/69/53/34, low-risk HPV6/11/32/40/44/70, and cutaneous HPV2/27/3/76 (titers 25–1, 000), and a vigorous CTL response. In vivo, mice were efficiently protected against experimental vaginal challenge with mucosal high-risk PsV types HPV16/18/45/31/33/52/58/35/39/51/59/68/56/73/26/53/66/34 and low-risk HPV6/43/44. Enduring protection was demonstrated 1 year after vaccination. RG1-VLP is a promising next-generation vaccine with broad efficacy against all relevant mucosal and also cutaneous HPV types.